Parenteral‐nutrition‐associated liver disease after intestinal perforation in extremely low‐birthweight infants: Consequent lethal portal hypertension. Issue 1 (14th February 2013) - Kubota, Akio; Mochizuki, Narutaka; Shiraishi, Jun; Nakayama, Masahiro; Kawahara, Hisayoshi; Yoneda, Akihiro; Tazuke, Yuko; Goda, Taro; Nakahata, Kengo; Sano, Hiroyuki; Hirano, Shinya; Kitajima, Hiroyuki
Abstract Background Parenteral nutrition (PN)‐associated liver dysfunction (PNALD) in term infants usually manifests as intrahepatic cholestasis, which recovers with enteral nutrition (EN) in most cases; however, as the number of extremely low‐birthweight infants (ELBWI) has been increasing, and consequently intestinal diseases associated with ELBWI have been increasing, more intractable PNALD has been encountered after surgical treatment in ELBWI, which does not resolve or rather worsens with EN. Methods Three cases of ELBWI with intestinal perforation, which developed PNALD and eventually died of hepatic failure with intractable portal hypertension, were reviewed. Their gestational age and birthweight ranged from 23 to 26 weeks, and from 434 to 968 g, respectively. The intestinal diseases included necrotizing enteritis in two and meconium‐related ileus with focal intestinal perforation in one. Results The duration of total PN without EN in the three cases was 17, 24 and 24 days, respectively. The interval between the introduction of PN and the onset of PNALD was 14, 4 and 18 days, respectively. A marked elevation of serum endotoxin level was detected in both cases of necrotizing enteritis. Histopathological study of the liver revealed marked cholestasis, significant hepatic necrosis with fibrosis, and proliferation of ductules in all these cases, which was responsible for portal hypertension. Conclusions PN after gastrointestinal disorders in ELBWI may cause refractory PNALD, which does not resolve, or rather worsens with the resumption of EN. Portal hypertension secondary to hepatic necrosis may be responsible for the exacerbation with the resumption of EN.